Analisis Spasial Kualitas Lingkungan Permukiman DanKondisi Kesehatan Masyarakat Dengan PemanfaatanPenginderaan Jauh Dan Sistem Informasi GeografisDi Kecamatan Serengan, Kota Surakarta - Kartanti, Dasih Widyaning, Drs. M. Musiyam, M.T.P, Agus Anggoro Sigit, S.Si., M.Sc (2015)
ABSTRACT Research of Environmental Quality and Public Health Conditions conducted in the District Serengan Surakarta aims to (1) determine the distribution of the quality of housing environment, (2) determine the distribution of public health conditions, (3) analysis of the spatial relationship of environmental quality residential and public health conditions. Survey method was used to test the accuracy of interpretation, the determination of sample survey using purposive sampling. This research uses descriptive quantitative method, based on remote sensing and geographic information systems, based on the interpretation process and deliver value or scoring. This study used some parameters as a determinant to know the environmental quality permukimanyaitu (1) the density of settlement, (2) a pattern layout of the building, (3) shade trees, (4) the width of the driveway, (5) the condition of the driveway, (6) residential location, (7) flood, (8) the quality of drinking water, (9) sanitation, (10) TPS and public health conditions parameter, namely (1) the crude mortality rate (CDR), (2) the crude birth rate (CBR), (3) The infant mortality rate (IMR), (4) morbidity (only dengue and diarrhea). The quality of housing environment class I (good) and the highest in Sub Kemlayan Kratonan village that is 100% better. The quality of housing environment class II (moderate) that is the highest in Sub Joyotakan 93.49%. The quality of housing environment Class III (bad) does not exist in the District Serengan. From 7 Village No 2 Village that have public health class I (good) ie Village Serengan and typhoid. There are 3 village that has a public health class II (moderate), namely the Village Jayengan, Joyotakan, and Kemlayan. For public health class III (bad) there are 2 Village namely Village Danukusuman and Kratonan. Overall in District Serengan between the quality of neighborhoods and public health conditions there are 45.33%, which is not directly proportional and there is 54.66% which is directly proportional.